SUSTAINABLE SUCCESS: HOW ENVIRONMENTAL PERFORMANCE DRIVES PROFITABILITY: A CASE STUDY IN SRI-KEHATI COMPANIES - Wardhiah; Rico Nur Ilham; Marzuki (PT. Radja Intercontinental Publishing, 2024)
The background of this research is based on the importance of environmental performance in improving the Company's image and seemingly towards sustainable profitability. This study aims to determine the influence of environmental performance on company profitability. This study uses a quantitative method with secondary data from the Company's financial statements. The data collection technique is carried out through documentation analysis, while the data analysis uses panel data analysis using E-Views. The population in this study consists of all companies listed in the SRI-Kehati Index, as many as 25 companies with a saturated sampling method that produces 75 observations. The results of the study show that partially, Environmental performance, ISO 14001 Certificate, and Environmental Cost have a positive and significant influence on the profitability of the Company. The conclusion of this study is to provide insight for managers and stakeholders about the importance of environmental performance in achieving the Company's financial performance.